2018
DOI: 10.2147/ijgm.s173253
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a do-not-resuscitate order on the quality of care in acute heart failure patients: a single-center cohort study

Abstract: BackgroundA do-not-resuscitate (DNR) order is reportedly associated with a decrease in performance measures, but it should not be applied to noncardiopulmonary resuscitation procedures. Good performance measures are associated with improvement in heart failure outcomes.AimTo analyze the influence of DNR order on performance measures of heart failure at our hospital, where lectures on DNR order are held every 3 months.DesignRetrospective cohort study.MethodsThe medical report of patients with acute heart failur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…We reported that, under these circumstances, a DNR order did not affect QOC measures of AHF patients, such as the rate of echocardiography, initiation of beta-blocker and ACEi or ARB for heart failure with reduced EF, and administration of anticoagulant for heart failure with atrial fibrillation. 7 Therefore, in this study, a worse QOC was less likely to explain the higher rate of oneyear mortality among DNR patients although we could not exclude the possibility that a DNR order leads to withholding unmeasured care which improves prognosis, with a resultant higher rate of one-year mortality. Another potential explanation for early DNR-associated increase in mortality of heart failure patients is that physicians often consider the prognosis when discussing advance directives, including DNR wishes, with patients and/or families.…”
Section: Discussionmentioning
confidence: 69%
See 3 more Smart Citations
“…We reported that, under these circumstances, a DNR order did not affect QOC measures of AHF patients, such as the rate of echocardiography, initiation of beta-blocker and ACEi or ARB for heart failure with reduced EF, and administration of anticoagulant for heart failure with atrial fibrillation. 7 Therefore, in this study, a worse QOC was less likely to explain the higher rate of oneyear mortality among DNR patients although we could not exclude the possibility that a DNR order leads to withholding unmeasured care which improves prognosis, with a resultant higher rate of one-year mortality. Another potential explanation for early DNR-associated increase in mortality of heart failure patients is that physicians often consider the prognosis when discussing advance directives, including DNR wishes, with patients and/or families.…”
Section: Discussionmentioning
confidence: 69%
“…The inhospital mortality of acute heart failure was 6% in our cohort. 7 Although it is not an ideal time to initiate ACP among patients who have never discussed it in the past, it may be the best time from that point on, because AHF can be a life-threatening condition. Furthermore, discussing code status on admission reportedly decreased invasive procedures before death that cancer 25 and non-cancer inpatients in an advanced stage would like to avoid.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To effectively use and prevent misuse of DNR orders, health professional must be educated about DNR 19 .…”
Section: Decision-making In Dnrmentioning
confidence: 99%